Utilization of tugi (Dioscorea esculenta) as a component of composite flour for the production of pan de sal. - Yadao, Jovelarne A.
Pan de sal holds great significance as a staple food in the Philippines, requiring multiple ingredients for its production. Among these ingredients, flour plays a critical role in terms of quantity. This research specifically examined the incorporation of tugi into composite flour for pan de sal, with potential applications for breadmaking. The study explored ten (10) different formulations consisting of all-purpose flour (APF), wheat flour (WF), and tugi flour (TF). The optimization of pan de sal relied on acceptability scores obtained from different parameters during the sensory evaluation. Texture profile and proximate analyses were performed on different treatments, including the optimized formulation. Tugi flour (TF) has cream to beige color with brown specks in the powder, a loose bulk density of 0.718, packed bulk density of 0.867, 5.57% moisture content, aw of 0.424, pH of 6.08, 27% increased foaming capacity, 2.20 g H2O/g TF water holding capacity, and 4.18 g H2O/g TF swelling capacity. TF's proximate composition was 5.57% moisture, 7.94% crude protein, 1.18% crude ash, 2.20±% crude fat, 1.69% crude fiber, and 81.91% carbohydrates. As TF amount increased, acceptability decreased with increased hardness and chewiness, while springness and cohesiveness decreased. The optimized formulation contained 14.21% APF, 70.07% WF, and 17.21% TF. A consumer preference test found no significant difference between the optimized formulation and commercial pan de sal. The proximate composition of the optimized pan de sal was 23.02% moisture, 11.48% crude protein, 1.74% crude ash, 15.44% crude fat, 1.09% crude fiber, and 47.23 carbohydrates. Pan de sal prices ranged from ₱1.97 to ₱4.18, while the optimized formula cost ₱1.86 per 15-g piece. Adding TF improved the nutritional composition and texture of pan de sal.